Pengaruh Kualitas Pelayanan dan Mobile Banking terhadap Kepuasan Nasabah Bank Syariah - Dina Zhafarina; Eneng Iviq Hairo Rahayu (Forum Kerjasama Pendidikan Tinggi, 2026)
Increasing competition in the Islamic banking industry has encouraged Bank Syariah Indonesia (BSI) to continuously improve service quality and mobile banking quality to enhance customer satisfaction. This study aims to analyze the effect of service quality and mobile banking quality on customer satisfaction at BSI KCP Jakarta Bona Indah, both partially and simultaneously. This research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 100 respondents selected using a purposive sampling technique. The data were analyzed using IBM SPSS Statistics 30 through validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results indicate that service quality has a positive and significant effect on customer satisfaction (t = 4.296; p < 0.001), while mobile banking quality also has a positive and significant effect on customer satisfaction (t = 6.161; p < 0.001). Simultaneously, both variables have a significant effect on customer satisfaction (F = 57.847; p < 0.001), with a coefficient of determination (R²) of 0.549, indicating that 54.9% of the variation in customer satisfaction is explained by service quality and mobile banking quality, while the remaining 45.1% is influenced by other factors outside this study. These findings suggest that improving service quality, supported by reliable, user-friendly, and secure mobile banking services, is an important strategy for enhancing customer satisfaction at BSI KCP Jakarta Bona Indah.